Legal Aspects of Reimbursement for Land and ROW in Transmission Construction Projects at PLN Central Sumatra - Erik Winada; Sami'an, Sami'an; Hardjomuljadi, Sarwono (International Journal of Law Policy and Governance, 2025)
Objective -This study aims to analyze the legal and contractual aspects related to the reimbursement scheme for land and ROW payments as a solution to completing transmission construction work during the Covid-19 pandemic. Methodology/Approach– This study uses a case study approach by analyzing contract documents, perception alignment, and related agreements between PLN and contractors. This study also examines the main elements of the contract in terms of the scope of work, with the addition of a reimbursement clause for land payments and ROW (Right of Way) at cost, as well as the addition of payment procedures.Findings– The results of this study indicate that the method of adding land reimbursement and ROW clauses to the agreement between the two parties can help complete transmission construction work according to the planned target, even though construction was underway during the Covid-19 pandemic, where the pandemic caused PLN to divert part of the budget to handling and controlling the impact of Covid on human resources, so that the budget for the work was temporarily constrained during the pandemic. Novelty/Benefits– This study provides an alternative solution to the completion of transmission construction work during the Covid-19 pandemic, where budget constraints can be overcome by adding a land and row reimbursement clause that will be paid at cost to partners. This alternative solution can also be a practical reference for transmission construction work owners during the pandemic